Coronary computed tomography angiography in pre-liver transplant cardiac work-up. (March 2023) - Manuli, C.; Saracco, M.; Lavezzo, B.; Calleri, A.; Depaoli, A.; D'Ascenzo, F.; Romagnoli, R.; Martini, S.
Abstract : Background: Controversies persist about the screening of pre-liver transplant(LT) patients for coronary artery disease(CAD). Dobutamine-stress-echocardiography(DSE) is used in many centers but it performs poorly. Coronary-computed-tomography-angiography(CCTA) is a promising tool to detect CAD and we aimed to describe its role in the the pre-LT setting. Materials and Methods: We included all patients who underwent CCTA during pre-LT work-up from 01/2022 to 11/2022 in our Centre. CCTA was performed in patients with at least one major cardiovascular risk factor (age>65 years, insulin-dependent diabetes, NASH-cirrhosis, severe peripheral vascular disease, previous stroke). Significant CAD(S-CAD) was defined as ≥50% stenosis in major-vessels or ≥70% stenosis in moderate-sized vessels. Patients with S-CAD or non-diagnostic CCTA underwent cardiac catheterization(CATH). Results: During the study period, 119 patients underwent pre-LT work-up in our Centre. CCTA was performed in 39/119(33%) patients, with median age 65 years (IQR 60-68): 22/39(56%) diabetics, 15/39(38%) with NASH-cirrhosis, 3/39(8%) peripheral vascular disease, 4/39(10%) previous stroke, 18/39(46%) arterial hypertension, 9/39(23%) dyslipidemia, 15/39(38%) active smokers. CCTA identified S-CAD in 15/39(38%) patients and was non-diagnostic in 2(5%); 14 of these 17 patients underwent CATH which diagnosed S-CAD needing revascularization in 7 patients. 6/7(86%) underwent percutaneous coronary intervention (PCI) (one complicated by myocardial infarction) with 1 month of dual-antiplatelet-therapy; 1/7(14%) required surgical-bypass. After revascularization: 2 patients were listed for LT, 1 died, 2 are still on dual-antiplatelet-therapy, 2 excluded from LT for extra-cardiac reasons. 2/7 patients before revascularization underwent DSE which tested negative. Until now, 10/22(45%) patients without S-CAD on CCTA underwent LT without early cardiological events and among the remaining 17 patients, 2 (S-CAD not requiring revascularization) underwent uneventful LT. Conclusions: In our pre-LT cohort with at least one cardiovascular risk factor, CCTA identified S-CAD in 15/39 patients (38%). 7 patients needed pre-LT PCI/bypass. CCTA appears to be a precious tool for detecting CAD in pre-LT work-up.